Molecular subtypes of breast cancer: distribution and prognostic implications - Salam Marouf, Shwan (Zanco Journal of Medical Sciences (ZJMS), 2025)
Background and objectives: Breast cancer is a heterogeneous disease complex with various molecular subtypes, each having unique features that significantly affect the disease’s course, behavior, treatment response, and prognosis. This study aimed to investigate the incidence of different breast cancer molecular subtypes and to explore the associations between these subtypes and important prognostic characteristics, such as tumor grade and disease stage. Methods: This study was a retrospective observational analysis of paper-based medical records of 187 female patients diagnosed with breast cancer and registered at the Oncology Center of Rizgary Teaching Hospital in Erbil City in 2021. Results: Analyzing the records of the 187 confirmed breast cancer patients revealed that luminal-B was the most frequent breast cancer molecular subtype, followed by luminal-A, TNBC and HER2-enriched subtypes in order of decreasing frequency. Additionally, the study found a statistically significant association between breast cancer molecular subtypes and prognostic characteristics such as tumor grade (P <0.001), primary tumor size (P = 0.017) and axillary lymph node status (P = 0.002). Conclusion: The findings revealed a significant association between different breast cancer molecular subtypes and key tumor characteristics such as tumor grade and TNM disease stage, potentially influencing therapeutic and prognostic outcomes.